The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10695-017-0365-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of different dietary organic acids on the growth, intestinal short-chain fatty acids, and liver histopathology of red hybrid tilapia (Oreochromis sp.) and potential use of these as preservatives

Abstract: Dietary organic acids are increasingly being investigated as a potential means of improving growth and nutrient utilization in aquatic animals. A 9-week study was performed to compare equal amounts (2%) of different organic acids (sodium butyrate, acetate, propionate, or formate) on the growth, muscle proximate composition, fatty acid composition, cholesterol and lipid peroxidation, differential cell counts, plasma biochemistry, intestinal short-chain fatty acid (SCFA) level, and liver histopathology to red hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…However, after performing a water exchange, the overall water quality became more stable and no abnormal liver histopathology was observed after another 3 weeks of culture. Moreover, the plasma bilirubin levels, which are indicators of liver function (Ebrahimi et al, ), were not significantly different by the end of the study. This indicated that bioflocs produced with either RRB or ResRB became better established.…”
Section: Discussionmentioning
confidence: 80%
“…However, after performing a water exchange, the overall water quality became more stable and no abnormal liver histopathology was observed after another 3 weeks of culture. Moreover, the plasma bilirubin levels, which are indicators of liver function (Ebrahimi et al, ), were not significantly different by the end of the study. This indicated that bioflocs produced with either RRB or ResRB became better established.…”
Section: Discussionmentioning
confidence: 80%
“…Several recent studies indicated that organic acids could alleviate oxidative stress status (Abdel-Salam et al, 2014;Ebrahimi et al, 2017;Li, Cui, & Leng, 2015;Romano et al, 2016;Zhang et al, 2016;Zhu, Qiu, Ding, Duan, & Wang, 2014). Besides, organic acids was also reported to beneficially modulate the intestinal microbiota and possess antimicrobial effects against several food-borne pathogens, such as Escherichia coli, Enterobacteria, Salmonella and Vibrio (Bosi et al, 1999;Canibe, Højberg, Højsgaard, & Jensen, 2005;Creus, Pérez, Peralta, Baucells, & Mateu, 2007;Partanen & Mroz, 1999;Silva, Vieira, Mouriño, Bolivar, & Seiffert, 2016;Zhou et al, 2009).…”
mentioning
confidence: 99%
“…However, in red hybrid tilapia (Ebrahimi et al . ), 2% of sodium butyrate, acetate, propionate or formate was shown to have no effect on the growth or feeding efficiency of the fish, a decrease in muscle lipid peroxidation and intestinal SCFAs, and induction of stress and compromised health was observed.…”
Section: Application Of Scfas In Aquaculturementioning
confidence: 90%
“…; Ebrahimi et al . ). Results from these studies have revealed that the type of prebiotic substrates, fermentation activity and the microbial populations associated with the process strongly affect the composition of fermentation end products.…”
Section: Factors Influencing the Formation Of Scfasmentioning
confidence: 97%
See 1 more Smart Citation